Pengungkapan carbon emission dan Kinerja Perusahaan: A Bibliometric Review - Utama, Reski Putra; Setiawan, Rahmat (Owner : Riset dan Jurnal Akuntansi, 2024)
Addressing global warming is an urgent challenge and an important agenda for humanity. This literature review uses bibliometrics to analyze nearly two decades of carbon emission reduction research in China, the largest carbon emitter. From 162 academic works published between 2009-2023, analysis with R-Studio and VOSviewer revealed basic characteristics, research strengths, topic evolution, and important research points. Results show increased attention and research on carbon emissions with the emergence of a stable core of institutions and journals. Although research disciplines are concentrated, research collaboration needs to be enhanced. Key research points include the causes, impacts, and consequences of carbon emissions, with evolving research boundaries.